The QDIS-7: using one scale to measure the disease-specific quality-of-life impact of different medical conditions - Shunichi Fukuhara; Joseph Green; Takafumi Wakita; Yosuke Yamamoto; Hajime Yamazaki; John E. Ware (Scientific Reports)
Abstract When measuring disease-specific quality of life (QOL), scores from different instruments can almost never be compared, so clinical and research questions involving more than one disease cannot be answered. To overcome that limitation, the Quality of Life Disease Impact Scale (QDIS-7) uses standardized content and only one metric. We tested whether QDIS-7 scores are comparable across diseases. In an online survey, 2,627 adults who had sought care for headache, low-back pain, asthma, or diabetes, responded to the QDIS-7 and to a previously-validated disease-specific QOL instrument (“legacy scale”) that measured QOL in their specific disease. Using the slopes of four independent regressions of legacy-scale scores on QDIS-7 scores, we tested the hypothesis that QDIS-7 scores can be compared across those four different medical conditions. The four regression-line slopes were nearly identical: 0.12 to 0.14 legacy-scale standard deviations per 1-point difference in QDIS-7 score. Thus, each 10-point difference in QDIS-7 scores was equal to slightly more than one standard-deviation difference in legacy-scale scores, for all four groups. The equivalence of the four slopes supports the use of the QDIS-7 to compare disease-specific QOL across different medical conditions. Thus, QDIS-7 users can answer clinical and research questions that are otherwise impossible to address.